Construcción de un electrodo activo y análisis técnico-económico. - Bravo Villacres, Wilson Renato (2019)
For the designing and construction of the active electrode relies on IEEE Std. 142-1991- BS 7430 1998 - NEC 6102410 regulations that establish lengths, materials, types of welding, chemicals and resistance values (Ω) in which it should be operate the active electrode, which has importance to safeguard the life of the operators and the protection of electrical and electronic equipment in case of overcurrents or overvoltages due to short circuits or atmospheric discharges. The objective of the designing and construction of the active electrode is to determine its efficiency through a comparison with a commercial active electrode, which will be installed in a homogeneous land that provides the same soil conditions (humidity-temperature-pH-granulometry-salinity). For technical analysis, the measurement of the resistivity of the ground and resistance in the active electrodes was made with the use of the SEW 4235 tellurometer. For economic analysis of the active electrodes, the construction consisted of the active electrode-prototype, applied chemicals In its installation and annual maintenance cost during its useful life, in the case of the commercial active electrode its acquisition cost, chemicals applied in its installation and annual maintenance cost were taken into account. With the results of the technical-economic analysis of the active electrodes was found that active-prototype electrode has better technical efficiency since it has a considerably lower resistance compared to the commercial electrode and the annual maintenance costs are relatively low in comparison with commercial electrode, thanks to its design that encapsulates chemicals causing its degradation later degradation and prolonging its efficiency longer.